O impacto do programa de recuperação fiscal na inadimplência tributária do Estado do Ceará - uma análise do antes e depois do REFIS estadual de 2009 - Castelo, André da Mota (2014)
In the attempt to receive credits due to the default of the taxpayers, the Union, the States and the Municipalities appeal to the programs of renegotiation of debts, REFIS. Since 2000 there have been more than five programs established by the Union, while in the State of Ceará since 1992 there have been more than ten programs. This almost regular frequency with which the programs are carried out may be creating a vicious behavior in which taxpayers in debt to the State regularize themselves when the programs are implemented and then return to defaulting once they expect another Program in the future will once again track unpaid debts. In order to identify the occurrence of this vicious circle, the econometric methodology of the "difference-difference estimator" was applied in a database from the years 2007 to 2011 of taxpayers from the State of Ceará, and the 2009 REFIS was considered as the base event for a comparison between before and after. In general terms, there is no significant impact of REFIS of 2009 on default. However, considering the heterogeneity of activities present in the base, it was observed that the REFIS 2009 induced an increase in the default, in average values per taxpayer, in the order of R$ 26.324,88 for the sector of "food production" , R$ 41.827,67 for the "wholesale trade, except motor vehicles and motorcycles" sector, R$ 7.238,94 for the "land transportation" sector. Similarly, there was a decrease in delinquency, in the order of 17.612,64 for the sector of "manufacturing of non-metallic minerals".